2015
DOI: 10.11646/zootaxa.4018.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Bicyclus ignobilis species-group (Lepidoptera: Nymphalidae: Satyrinae) with descriptions of two new species

Abstract: The ignobilis-group of the genus Bicyclus Kirby 1871 is revised. The species-group contains six species with a distinct wing pattern, but limited intraspecific variation, distributed across tropical African rainforest. We investigate a set of more than 1000 specimens from a range of museum collections, including some type material, and thoroughly update the biogeographical knowledge for the group. We also describe two new species as members of the group. The included species are: Bicyclus ignobilis (Butler 187… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The rate of androconial evolution in butterflies is a promising field for future research, and highly variable patterns are found even within Bicyclus . Comparing the sciathis group with another recently revised species group, the ignobilis group (Brattström et al , 2015), substantial differences can be seen. Both groups are of a similar evolutionary age (Aduse‐Poku et al , ), occur in the same type of wet evergreen forest habitat and have similar distributional borders.…”
Section: Discussionmentioning
confidence: 94%
“…The rate of androconial evolution in butterflies is a promising field for future research, and highly variable patterns are found even within Bicyclus . Comparing the sciathis group with another recently revised species group, the ignobilis group (Brattström et al , 2015), substantial differences can be seen. Both groups are of a similar evolutionary age (Aduse‐Poku et al , ), occur in the same type of wet evergreen forest habitat and have similar distributional borders.…”
Section: Discussionmentioning
confidence: 94%
“…For character sampling, hindwings and forewings of the different Bicyclus and outgroup species were imaged using a Leica DMS 1000 microscope. The images in combination with data from Condamin (Condamin 1973) and other scientific literature (Nieberding et al 2008;Bacquet et al 2015;Brattström et al 2015Brattström et al , 2016Aduse-Poku et al 2017) were used to score the presence and absence of hair-pencils and scent patches in each species. We defined a hair-pencil as a group of tightly packed brush-like scales.…”
Section: Animal Husbandrymentioning
confidence: 99%
“…On the other hand, many species in the tribe Satyrini possess scent organs consisting of hairpencils (Fig 1 A,B) and scent patches (Fig 2A), both on the wing, that brush against each other dispersing chemicals in the process (Nieberding et al 2008;Brattström et al 2015Brattström et al , 2016Aduse-Poku et al 2017). It is to be noted however, that glandular, secretory cells underly some of the patches and produce pheromones, while other patches are not associated with such secretory cells (Bacquet et al 2015;Dion et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012 Brattstr€ om described the species B. brakefieldi from Democratic Republic of Congo. Recently Brattstr€ om, AdusePoku, Collins, and Brakefield (2015) and Brattstr€ om, Aduse-Poku, Collins, Di Micco de Santo, and Brakefield (2016) published two revisions of Bicyclus species groups describing six further species: B. ottossoni and B. vandweghei in 2015 and B. elishiae, B. heathi, B. sigiussidorum, and B. subtilisurae in 2016. In the 2015 paper all subspecies of B. ignobilis were also synonymized with the nominate form.…”
Section: Introductionmentioning
confidence: 99%